2020
DOI: 10.1002/advs.202001722
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Stable 2D Intrinsic Ferromagnetic Ta3FeS6 with Four Months Durability

Abstract: 2D ferromagnetic materials provide an important platform for the fundamental magnetic research at atomic-layer thickness which has great prospects for next-generation spintronic devices. However, the currently discovered 2D ferromagnetic materials (such as, CrI 3 , Cr 2 Ge 2 Te 6 , and Fe 3 GeTe 2) suffer from poor air stability, which hinders their practical application. Herein, intrinsic long-range ferromagnetic order in 2D Ta 3 FeS 6 is reported, which exhibits ultrahigh stability under the atmospheric envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…[ 14 ] Similar to conventional vdW magnets, the intercalated TMDCs are cleavable and maintain long‐range magnetic order even down to 2D scale. [ 15–17 ] More importantly, if the intercalator concentration is precisely controlled at x = 1/3 in T x MX 2 (T = V, Cr, Mn, Fe, Co, Ni; M = Nb, Ta; X = S, Se), the entire system forms a noncentrosymmetric chiral crystal structure ( P 6 3 22 space group), although its parent compound MX 2 is centrosymmetric non‐chiral. [ 18 ] The amalgamation of long‐rang magnetic order and crystal chirality in T x MX 2 may promote interesting spin textures, such as magnetic solitons.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Similar to conventional vdW magnets, the intercalated TMDCs are cleavable and maintain long‐range magnetic order even down to 2D scale. [ 15–17 ] More importantly, if the intercalator concentration is precisely controlled at x = 1/3 in T x MX 2 (T = V, Cr, Mn, Fe, Co, Ni; M = Nb, Ta; X = S, Se), the entire system forms a noncentrosymmetric chiral crystal structure ( P 6 3 22 space group), although its parent compound MX 2 is centrosymmetric non‐chiral. [ 18 ] The amalgamation of long‐rang magnetic order and crystal chirality in T x MX 2 may promote interesting spin textures, such as magnetic solitons.…”
Section: Introductionmentioning
confidence: 99%
“…Ternary GVTMCs show more abundant magnetic states owing to their extra component freedom, such as hard ferromagnet Ta 3 FeS 6 , Ta 4 FeS 8 , chiral helimagnet Nb 3 CrS 6 , and spin glass NbFeTe 2 . [ 45,46,54,56,75–80 ] Morosan and co‐workers demonstrated the strong magnetic anisotropy in Ta 4 FeS 8 via anisotropic magnetotransport measurements. [ 80 ] They found that the magnetic moments of Ta 4 FeS 8 are parallelly aligned along the c ‐axis and exhibit sharp switching behavior under the out‐plane magnetic field with Curie temperature of 160 K. [ 80 ] Further, Park and co‐workers demonstrated the Ruderman–Kittel–Kasuya–Yosida magnetic coupling with Ising‐type spin states in Ta 4 FeS 8 .…”
Section: Structures and Propertiesmentioning
confidence: 99%
“…[ 56 ] Recently, Zhai and co‐workers revealed the intrinsic ferromagnetism in 2D Ta 3 FeS 6 . [ 46 ] They found that the few‐layer Ta 3 FeS 6 shows giant magneto‐optical Kerr effect and ultrahigh air stability with 4 months durability. [ 46 ] More intriguing, chiral magnetic orders are observed in Nb 3 CrS 6 which has unique magnetic soliton lattice.…”
Section: Structures and Propertiesmentioning
confidence: 99%
See 2 more Smart Citations